Association between donor age and risk of graft failure after liver transplantation: an analysis of the Eurotransplant database. (31st October 2018) - Pratschke, Sebastian; Bender, Andreas; Boesch, Florian; Andrassy, Joachim; van Rosmalen, Marieke; Samuel, Undine; Rogiers, Xavier; Meiser, Bruno; Küchenhoff, Helmut; Driesslein, David; Werner, Jens; Guba, Markus; et al.
Summary: Grafts from elderly donors are increasingly used for liver transplantation. As of yet there is no published systematic data to guide the use of specific age cutoffs the effect of elderly donors on patient outcomes must be clarified. This study analyzed the Eurotransplant database (01/01/2000–31/07/2014; N = 26 294) out of whom 8341 liver transplantations were filtered to identify for this analysis. 2162 of the grafts came from donors >60 including 203 from octogenarians ≥80 years. Primary outcome was the risk of graft failure according to donor age using a confounder adjusted Cox‐Regression model with frailty terms (or random effects). The proportion of elderly grafts increased during the study period [i.e., octogenarians 0.1% ( n = 1) in 2000 to 3.4% ( n = 45) in 2013]. Kaplan–Meier and Cox‐analyses revealed a reduced survival and a higher risk for graft failure with increasing donor age. Although the age effect was allowed to vary non‐linearly, a linear association hazard ratio (HR = 1.1 for a 10 year increase in donor age) was evident. The linearity of the association suggests that there is no particular age at which the effect increases more rapidly, providing no evidence for a cutoff age. In clinical practice, the combination of high donor age with HU‐transplantations, hepatitis C, high MELD‐scores and long cold ischemic time should be avoided.